Assessment of Suvorexant and Eszopiclone as Alternatives to Benzodiazepines for Treating Insomnia in Patients With Major Depressive Disorder. Issue 3 (14th May 2022) - Shigetsura, Yuki; Imai, Satoshi; Endo, Hiroki; Shimizu, Yumi; Ueda, Keita; Murai, Toshiya; Itohara, Kotaro; Nakagawa, Shunsaku; Yonezawa, Atsushi; Ikemi, Yasuaki; Fukatsu, Sachio; Kitada, Noriaki; et al.
Abstract : Objectives: We investigated the utility of switching from benzodiazepines to suvorexant or eszopiclone to manage benzodiazepine-unresponsive insomnia in patients with major depressive disorder (MDD) in a randomized, open-label study. Methods: Patients with MDD who have insomnia symptoms (a score of >7 on the Insomnia Severity Index Japanese version [ISI-J]), who had received benzodiazepine treatment for more than 2 weeks (n = 18) were randomized to 4 weeks of suvorexant (20 or 15 mg/d) or eszopiclone (3 or 2 mg/d) treatment. The primary endpoint was an improvement in insomnia severity from baseline assessed by the ISI-J score at 2 and 4 weeks after switching from benzodiazepines. The secondary endpoints included changes in the scores of the Pittsburgh Sleep Quality Index Japanese version, the Beck Depression Inventory II, Generalized Anxiety Disorder 7, the digit span test, and the digit symbol substitution test from baseline. Adverse events were recorded throughout the study. Results: Patients taking suvorexant or eszopiclone had improved ISI-J scores (−4.3 for suvorexant and −4.1 for eszopiclone at week 4; P = 0.04 for eszopiclone). Both drugs tended to improve the Beck Depression Inventory II and Generalized Anxiety Disorder 7 scores 2 and 4 weeks after switching. The Pittsburgh Sleep Quality Index Japanese version, digit symbol substitution test, and digit span test scores and the incidence of adverse events did not change from baseline. Conclusions: Switching to suvorexant or eszopiclone was well tolerated and improved the severity of benzodiazepine-unresponsive insomnia in MDD patients. Both drugs could be beneficial alternatives to benzodiazepines for treating insomnia in MDD patients.